Physical and chemical data from a firn aquifer in Southeast Greenland, 2015-2016 - Olivia Miller; Kip Solomon; Clement Miege; Richard Forster; Lora Koenig (Arctic Data Center, 2019)
This dataset includes physical and chemical data from a firn aquifer upslope from Helheim Glacier collected in 2015 and 2016 to advance understanding of aquifers forming within the firn (compacted snow) of the percolation zone of the Greenland ice sheet. The dataset includes depth-specific tritium and CFC-11 measurements in aquifer liquid water and tritium in firn, dye concentration from a tracer experiment, firn core density and stratigraphy, and time series of firn temperature and pressure transducer recordings. The tritium and CFC-11 data constrain aquifer age. The dye experiment provides information on meltwater movement through the unsaturated zone. Firn density and stratigraphy provide insight into snow accumulation and compaction, as well as melt patterns. Pressure transducer data was used to monitor water levels over time. Firn temperature indicates the thermal state of the aquifer and is useful for modeling the aquifer.